(untitled) (Research, Society and Development, 2020)
Waste from health services represents a major public and environmental health problem in Brazil and within health, institutions there are still wrong practices regarding correct management. The study aimed to evaluate the knowledge about the Waste Management of Health Services among professionals of the Basic Health Units in the city of Guaraí, Tocantins, Brazil. This is a descriptive, exploratory study with a quali-quantitative approach. The interviews were conducted with 89 health workers, comprising a sample of 26 (29%) professional nurses, dentists and doctors, and 63 (71%), high school professionals (community health agents, nursing technicians and health technicians). oral). Among workers with higher education 25 (96,1%) correctly conceptualized SSR, thus demonstrating knowledge about the subject, however, among workers with high school 48 (76,1%) gave an assertive answer, drawing attention in this group the fact that 15 (23,8%) did not answer the question correctly. Regarding the question whether the respondent’s work institution conducts training on Health Care Waste, 23 (88,4%) of workers with higher education, and 51 (80,9%) of workers with high school said “no” in your answers. Workers with high school should receive training, as they have less mastery on the subject. Healthcare waste is still understood as hospital waste by most questionnaires and sharps are the most mentioned.